Acute and Chronic Toxicity of Nickel and Zinc to a Laboratory Cultured Mayfly (Neocloeon triangulifer) in Aqueous but Fed Exposures. (26th April 2020) - Soucek, David J.; Dickinson, Amy; Schlekat, Chris; Van Genderen, Eric; Hammer, Edward J.
Abstract: Aquatic insects are poorly represented in water quality criteria, and previous studies have suggested a lack of sensitivity in acute toxicity tests despite observational studies demonstrating the contrary. Our objectives were to determine the toxicity of nickel (Ni) and zinc (Zn) to the mayfly Neocloeon triangulifer in fed acute (96‐h) and chronic exposures to estimate aqueous effect concentrations while acknowledging the importance of dietary exposure for these insects. For the chronic tests, we conducted preliminary full–life cycle (~25–30 d) and subchronic (14 d) exposures to compare the relative sensitivity of the 2 test durations under similar conditions (i.e., feeding rates). Observing similar sensitivity, we settled on 14 d as the definitive test duration. Furthermore, we conducted experiments to determine how much food could be added to a given volume of water while minimally impacting dissolved metal recovery; a ratio of food dry mass to water volume (<0.005) achieved this. In the 14‐d tests, we obtained a median lethal concentration and most sensitive chronic endpoint of 147 and 23 µg/L dissolved Ni (acute to chronic ratio [ACR] = 6.4), respectively, and 81 (mean value) and 10 µg/L dissolved Zn (ACR = 8.1), respectively. The acute values are orders of magnitude lower than previously published values for mayflies, probably most importantly due to the presence of dietary exposure but also potentially with some influence of organism age and test temperature. Environ Toxicol Chem 2020;39:1196–1206. © 2020 SETAC